PENGARUH VARIASI LATIHAN TERHADAP HASIL SHOOTING DALAM PERMAINAN SEPAK BOLA - Andreas, Andreas; Atiq, Ahmad; Bafadal, M. Fachrurrozi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to improve the basic technique of shooting at the goal in a soccer game with a variety of exercises for players or players who take part in soccer extracurriculars at SMA N 8 Pontianak. -post test design and use shooting test instruments at the goal. The sample of this study was all football players who took part in extracurricular football at SMA N 8 Pontianak, totaling 20 people with the technique of saturated sampling technique. Based on the results of the research, the initial test shooting data at the goal was a score of 156 with an average of 7.8 and the final test increased to 219 with an average value of 10.95, thus there was an increase in the shooting test towards the goal, which was 3.15% from the initial test. The statistical test T count is greater than T tabe tau 4.55 2.093, so there is an effect of variation training on the basic technique of shooting at the goal in soccer games, with the variation of training, players will always repeat and kick towards the goal in accordance with trainer's instructions and experience.Keywords: Practice Variations, Basic Soccer Shooting Technique